THE FACTORS THAT INFLUENCE THE SELECTION OF CAREER AS PUBLIC ACCOUNTANT AND NON-PUBLIC ACCOUNTANT (Study of Accounting Student University Bengkulu) - Madani Hatta; Meli Sartika (UNIB Press, 2016)
The aim of this research is to know and analyzes the factors that influence the selection of career interestas public accountant and non-public accountant in terms of financial award, professional training, professionalrecognition, social values, work environment, job market considerations and personality. This research is empiricalresearch with qualitative approach which involves the use of statistical analysis. This research is using the primarydata. The tool used in this research is logistic regression with SPSS software version 16. The results of this researchshow that the financial award, professional training and social values has an influence on the selection of career aspublic accountant and non-public accountant but for professional recognition, work environment, job marketconsideration and personality doesn’t influence the selection of a career as a public accountant and a non-publicaccounting.Key words: accountant, financial award, professional training, professional recognition, social values, workenvironment, job market consideration and personality.